Specialized post-inpatient psychotherapy for sustained recovery in anorexia nervosa via videoconference: study protocol of the randomized controlled SUSTAIN trial - Giel, Katrin; Martus, Peter; Schag, Kathrin; Herpertz, Stephan; Hofmann, Tobias; Schneider, Antonius; Teufel, Martin; Voderholzer, Ulrich; Wietersheim, Jörn von; Wild, Beate; Zeeck, Almut; Bethge, Wolfgang Andreas; et al. (Journal of eating disorders, 2021)
A major barrier to long-term recovery from anorexia nervosa (AN) are early and frequent relapses after inpatient treatment. There is an urgent need for enhanced continuity of specialized care involving effective aftercare interventions and relapse prevention strategies in order to improve the long-term outcome for patients with AN.
Gesehen am 16.08.2021